EFEKTIVITAS PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS EKSPERIMEN PADA MATERI SISTEM PERNAPASAN DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XI SMA(THE EFFECTIVENESS OF STUDENT WORKSHEETS ON RESPIRATORY SYSTEM IN IMPROVING THE LEARNING OUTCOMES OF 11th GRADE HIGH SCHOOL STUDENTS) - Akmala, Muthia; Hidayah, Rizka Rifaatul; Zaliani, Indah; Aulia, Aida Rahma; Suryanda, Ade; Safitri, Dini; Pusparini, Fitria (Jurnal Edukasi Biologi, 2025)
21st-century learning outcomes are important in preparing individuals to face the challenges of the modern world, especially in science learning. Factors influencing learning outcomes include learning media, such as Student Worksheets (LKPD), which help students understand the material better. This study used the Research and Development (R&D) method with the 4D model from Thiagarajan and Semmel, including the Define, Design, Develop, and Disseminate stages. The sampling technique used is purposive sampling. A small-scale trial was conducted on 30 grade XI students of SMAN 70 Jakarta. The results of the expert feasibility assessment showed that the material aspect scored 82%, the media aspect 84%, and the language aspect 80%, so the LKPD was declared feasible to use. The assessment of the practicality of the LKPD was measured using a response questionnaire sheet, which obtained very practical results. In addition, the results showed an average pre-test score of 76.6 and a post-test of 95.6, which showed a significant increase in student understanding. The development of LKPD based on experiments on the respiratory system material has proven effective in improving student learning outcomes. This study confirms that using experiment-based LKPD can support learning optimally, combining theory and practice to improve student understanding.